Role of farming awareness in crop pest management - A mathematical model. (14th January 2019) - Basir, Fahad Al; Banerjee, Arnab; Ray, Santanu
Highlights: Crop pest management and farming awareness are equally important issues in agriculture. The growth of awareness level is proportional to the density of pest in the crop field. Global source such as radio, TV etc. can increase the level of awareness among people. Aware people adopt control methods namelybio-pesticides/integrated pest management. Raising awareness among people with tolerable time delay isrequired forpest control. Abstract: Control of pest attack is an important aspect in agriculture to obtain healthy crop as well as high yield. Farming awareness is also equally important in pest management. Awareness campaign are made for making people aware of damages due to the pest and protect the crop from pests which ultimately leads to high crop yield. In this article, a mathematical model is proposed to study the effect of awareness among the people in crop pest management using plant biomass, pest and aware population. Pest population is divided into two compartments: susceptible pest and infected pest. We assume that the growth of awareness level is assumed to be proportional to the density of healthy pest in the crop field. Global source such as radio, TV etc. can increase the level of awareness. It is further assumed that aware people will adopt biological control methods like integrated pest management. Susceptible pests are made infected by this process as infected pest are less harmful to crop. Moreover, there may be some time delay in measuring the healthy pests in the crop field i.e. some delay may take place in taking necessary steps while controlling the pest attack. Thus we developed the model incorporating time delay into the system. The existence and the stability criteria of the equilibria are obtained in terms of the basic reproduction number. The Hopf-bifurcation analysis has been done at the endemic equilibrium considering time delay as the bifurcation parameter. Numerical simulations are carried out to justify the analytical results.